OCLC library holdings: assessing availability of academic books in libraries in print and electronic compared to citations and altmetrics - Maleki Ashraf (Springer Nature, 2022)
Although library holding data is constructed upon work format of books, it is less known how much print and electronic books in libraries contribute to the library holding counts. In response, this research is an attempt to explore the distribution of library holding data across work formats and investigate the availability of library print holdings and library electronic holdings for books as constituents of the library holding metric across fields and over time and compared with other book metrics. ISBNs, titles and author names of 119,794 Scopus-indexed book titles across 26 fields were examined for fourteen variables including OCLC Library Holdings, Scopus Citations, Google Books Citations, Goodreads engagements, and Altmetric indicators. There are three major findings: (a) library holdings are a more comprehensively available metric for books (over 97%) than any other metric and could be useful after short time after first edition publication, followed by Google Books, Goodreads and Scopus, respectively; (b) on average electronic holdings are seven times (median three times) more numerous than print holdings and their ratio is growing considerably for more recent books; (c) there is consistent downward trend in average print book holdings, suggesting that library print holding data are cumulative in nature and statistically comparable to formal citations; however, acquisition of electronic books in libraries is inconsistent in distribution plot as well as over time. In sum, the differences between print and electronic holding data are broad making them distinct metrics, suggesting that further research is needed for understanding their implications for book impact assessment.